Incidence of bacteraemia after urodynamic study - Onur, R; Özden, M; Orhan, I; Kalkan, A; Semercioz, A (W B Saunders Co Ltd, 2004)
The aim of the present study was to determine the incidence of bacteraemia after urodynamic study (UDS) in patients with lower urinary tract symptoms, and to evaluate the role of bacteraemia as a morbidity factor related to UDS. A total of 57 patients (mean age: 52.8 years, range: 8-76 years) were evaluated by UDS. Prophylactic antibiotics were not administered to any of the patients before the procedure. Before UDS, urine cultures were examined for the presence of infection of the urinary tract (UTI). Venous blood was taken before and just after performing UDS. There was no bacterial. growth in blood cultures of any patients before the UDS. Of the 57 patients, two had bacteriuria before study. After UDS, bacteraemia was determined in four (7%) out of 55 patients. The two patients with a bacteriuria before the procedure also had positive blood cultures. Infectious complications are the most important morbidity factors related to the UDS. Despite the use of strict aseptic techniques, bacteraemia may occur in patients undergoing UDS. The results of the present study may help when counselling patients who are to undergo UDS. (C) 2004 The Hospital Infection Society. Published by Elsevier Ltd. All rights reserved.
Keywords: urodynamic study; bacteraemia; incidence